Inherent dynamics within the Crimean‐Congo Hemorrhagic fever virus protease are localized to the same region as substrate interactions. (28th January 2015) - Eisenmesser, Elan Z.; Capodagli, Glenn C.; Armstrong, Geoffrey S.; Holliday, Michael J.; Isern, Nancy G.; Zhang, Fengli; Pegan, Scott D.
Abstract: Crimean‐Congo Hemorrhagic fever virus (CCHFV) is one of several lethal viruses that encodes for a viral ovarian tumor domain (vOTU), which serves to cleave and remove ubiquitin (Ub) and interferon stimulated gene product 15 (ISG15) from numerous proteins involved in cellular signaling. Such manipulation of the host cell machinery serves to downregulate the host response and, therefore, complete characterization of these proteases is important. While several structures of the CCHFV vOTU protease have been solved, both free and bound to Ub and ISG15, few structural differences have been found and little insight has been gained as to the structural plasticity of this protease. Therefore, we have used NMR relaxation experiments to probe the dynamics of CCHFV vOTU, both alone and in complex with Ub, discovering a highly dynamic protease that exhibits conformational exchange within the same regions found to engage its Ub substrate. These experiments reveal a structural plasticity around the N‐terminal regions of CCHFV vOTU, which are unique to vOTUs, and provide a rationale for engaging multiple substrates with the same binding site.